Pengaruh Pengaruh Jenis Bahan Atap Terhadap Intensitas Medan Elektromagnetik ELF Oleh SUTET 500 KV - Wati, Lisa Listyo; Prihandono, Trapsilo; Sudarti (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
Based on initial observations, Kersikan Village is passed by the 500 kV SUTET transmission line which is very close to residents' homes. The purpose of this study is to analyze whether the type of roofing material and the distance of the study have an effect in reducing the intensity of the ELF electromagnetic field by the 500 kV SUTET. The type of research used is quantitative research using survey techniques. In this study, there are 2 dependent variables, namely ELF magnetic field intensity and ELF electric field intensity. Artificial houses are used to test the effect of roof type on ELF electromagnetic intensity. The research data was measured from morning to night and the measurement distance was getting farther from SUTET. Based on the results obtained, the intensity of the electric field and ELF magnetic field without a roof barrier around the SUTET decreased when compared to measurements under the roof and the biggest decrease occurred when under the galvalume roof. Measurements at a distance of 0 meters obtained greater intensity results than when measuring distances of 50 and 100 meters. The measurements in the morning produced a smaller magnetic field intensity and electric field than the measurements at night. So it can be concluded that there is an effect of roof type, distance and measurement time on the intensity of ELF electromagnetic fields around SUTET.